2014
DOI: 10.1371/journal.pone.0094637
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Interleukin-9 Correlate with Negative Prognostic Factors in Extranodal NK/T-Cell Lymphoma

Abstract: Interleukin-9 (IL-9) is more functionally diverse than previously expected, especially with regards to lymphomagenesis. However, the relationship between IL-9 and the clinicopathological features of extranodal NK/T-cell lymphoma is less well established. Patients with this lymphoma in Sun Yat-Sen University Cancer Center between January 2003 and March 2013 were systematically reviewed in an intention-to-treat analysis. Baseline serum IL-9 levels were determined using sandwich enzyme-linked immunosorbent assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…This retrospective study analyzed the clinical characteristics of patients with ENKL. In agreement with previous studies (2,13), our data demonstrated that ECOG score, stage, IPI, presence of B symptoms and treatment with radiotherapy were independently associated with the survival of ENKL. However, the LDH level did not exhibit an independent association with survival, which differed from the results of other studies (1,8), despite the fact that the mOS of patients with elevated serum LDH was below average (70 vs. 96 months) (Table I).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This retrospective study analyzed the clinical characteristics of patients with ENKL. In agreement with previous studies (2,13), our data demonstrated that ECOG score, stage, IPI, presence of B symptoms and treatment with radiotherapy were independently associated with the survival of ENKL. However, the LDH level did not exhibit an independent association with survival, which differed from the results of other studies (1,8), despite the fact that the mOS of patients with elevated serum LDH was below average (70 vs. 96 months) (Table I).…”
Section: Discussionsupporting
confidence: 93%
“…Extranodal natural killer-T cell lymphoma (ENKL) is a subtype of non-Hodgkin lymphoma (1), occurring more frequently in Asia compared with Western countries (2). According to a recent survey, ENKL is the second most common extranodal lymphoma subtype in China after large B-cell lymphoma (3).…”
Section: Introductionmentioning
confidence: 99%
“…35 Biomarkers associated with poor prognosis included the expression of p53 and p63, and high serum levels of interleukin-9, CXCL13, serum VEGF, and survivin. [36][37][38][39] EBV-encoded latent membrane protein expression correlated with the phosphorylation of RelA and Akt possibly had a favorable impact on clinical outcome in patients with ENKTLs. 20,40 Among pathology parameters, an adverse prognosis was correlated with a high Ki-67 labeling index and EBV DNA load but not with cellular morphology or the expression of CD56.…”
Section: Modern Pathology (2016) 29 430-443mentioning
confidence: 99%
“…IL-9 has long been recognized as an important growth and differentiation factor for transformed lymphoid cells, including malignant T cells [58–61]. In addition, IL-9 is also capable of modulating the inflammatory microenvironment of lymphoid tumors [62].…”
Section: Th9 Cells In Skin Disordersmentioning
confidence: 99%